2022
DOI: 10.1093/geront/gnac115
|View full text |Cite
|
Sign up to set email alerts
|

Automated Vehicles for People With Dementia: A “Tremendous Potential” That “Has Ways to go”―Reports of a Qualitative Study

Abstract: Background and Objectives The prospect of automated vehicles (AV) has generated excitement among the public and the research community about their potential to sustain the safe driving of people with dementia. However, no study to date has assessed the views of people with dementia on whether AVs may address their driving challenges. Research Design and Methods This mixed-methods study included two phases, completed by nine p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Research has shown that older adults often experience a decline in travel frequency, an increase in travel time, and a decrease in travel distance with age (22). At the same time, the driving ability of older individuals is also affected by age, which further increases traffic risks (10).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that older adults often experience a decline in travel frequency, an increase in travel time, and a decrease in travel distance with age (22). At the same time, the driving ability of older individuals is also affected by age, which further increases traffic risks (10).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This can manifest as difficulties in using traditional public transportation, cessation of driving (7,8), and encountering transportation challenges that may lead to social exclusion (9). At the same time, age affects driving ability, which can increase traffic risk (10). Crash statistics also indicate that older drivers are more vulnerable in crash situations and pose a risk to themselves and other traffic participants (11,12).…”
Section: Introductionmentioning
confidence: 99%